If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + 5n = 27 + 3n Solving 17 + 5n = 27 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 17 + 5n + -3n = 27 + 3n + -3n Combine like terms: 5n + -3n = 2n 17 + 2n = 27 + 3n + -3n Combine like terms: 3n + -3n = 0 17 + 2n = 27 + 0 17 + 2n = 27 Add '-17' to each side of the equation. 17 + -17 + 2n = 27 + -17 Combine like terms: 17 + -17 = 0 0 + 2n = 27 + -17 2n = 27 + -17 Combine like terms: 27 + -17 = 10 2n = 10 Divide each side by '2'. n = 5 Simplifying n = 5
| 36t-72=12t-12 | | y=3(x^4)/4+384 | | ((2x+1)/(x+2))+3 | | (2x+1/(x+2))+3=0 | | y=375+0.8(y-15-0.25y+60)-20r | | 4n+3=17+n | | (3x+7)(7x+10)/8=0 | | 1.428571429/8 | | 6+3n=5n-2 | | (3x+7)(7x+10)=0 | | 5+3n=5n-3 | | 21x^2+30x+49x+70=0 | | 3/4x-6+1/3x-1 | | 3/4t-6+1/3t-1 | | (21x^2+30x+49x+70)/8 | | 12-3y=-4x | | 5a-20=10a+5 | | (3x+7)(7x+10)/8 | | 7x-19=0 | | (3x-2y+3)dy+(3x-2y+1)dx=0 | | 8x+12-7=13 | | y=-4/3x^3 | | (6w^3)/(w+2) | | (9+y)(4y-3)=0 | | 12(c/2)=6c | | 12(c/2)=6(c) | | 5x-10=-12 | | 13(2m+2c-4h)= | | 4(h+3)= | | 14h+36=148 | | -3.35=60/4 | | -u-4u=-100 |